Effect of ASP flooding on oil-water stabilization and separation - Khan, J.A. (Asian Research Publishing Network, 2016)
The effectiveness of the nature of the ASP on the zeta potential, growth of mean droplet size and viscosity of emulsions have been investigated. Water in oil based emulsion was prepared and inspected the emulsion stability by analysing droplet zeta potential, growth of drop size and viscosity. An electric mechanism of dispersed phase stabilization is projected to make clear the long term stability observed for EOR implemented fields in Malaysia. Experiments results of droplet zeta potential for the different emulsions, showed that emulsions with low concentration of alkaline, polymer and high concentration of surfactant observed strong stability. By contrast, ASP stabilized emulsions of high alkaline, polymer and low surfactant, formed less stable emulsions. Cross polarized measurements were performed to analyse the drop size of water dispersed in oil stabilized at various compositions of ASP. The growth of drop sizes showed linear like behaviour with droplets zeta potential tests. Present results show that viscosity is not effected by temperature. It is also observed that increase in salinity concentration is contributing in the separation. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.